Physical activity predicts quality of life and happiness in children and adolescents with cerebral palsy. Issue 9 (23rd April 2016) - Maher, Carol Ann; Toohey, Monica; Ferguson, Monika
Abstract: Purpose : To examine the associations between physical activity, health-related quality of life and happiness in young people with cerebral palsy. Method : A total of 70 young people with cerebral palsy (45 males, 25 females; mean age 13 years 11 months, SD 2 years 0 month) took part in a cross-sectional, descriptive postal survey assessing physical activity (Physical Activity Questionnaire for Adolescents), functional ability (Gross Motor Function Classification System), quality of life (Pediatric Quality of Life Inventory 4.0) and happiness (single Likert-scale item). Relationships between physical activity, quality of life and happiness were examined using backward stepwise linear regression. Results : Physical activity significantly predicted physical quality of life ( R 2 = 0.64, β = 6.12, p = 0.02), social quality of life ( R 2 = 0.28, β = 9.27, p < 0.01) and happiness ( R 2 = 0.08, β = 0.9, p = 0.04). Physical activity was not associated with emotional or school quality of life. Conclusions : This study found a positive association between physical activity, social and physical quality of life, and happiness in young people with cerebral palsy. Findings underscore the potential benefits of physical activity for the wellbeing of young people with cerebral palsy, in addition to its well-recognised physical and health benefits. Implications for Rehabilitation: Physical activity is a key predictor of quality of life and happiness in young people with cerebral palsy. Physical activity is widely recognised as having physical health benefits for young people with cerebral palsy; however, this study also highlights that it may have important benefits for wellbeing, quality of life and happiness. This emphasises the need for clinical services and intervention studies aimed specifically at increasing physical activity amongst children and adolescents with cerebral palsy.